The Significance of Different Diacylgycerol Synthesis Pathways on Plant Oil Composition and Bioengineering - Bates, Philip D.; Browse, John (Frontiers in Plant Science, 2012)
The unique properties of vegetable oils from different plants utilized for food, industrial feedstocks, and fuel is dependent on the fatty acid (FA) composition of triacylglycerol (TAG). Plants can use two main pathways to produce diacylglycerol (DAG), the immediate precursor molecule to TAG synthesis: 1) De novo DAG synthesis, and 2) conversion of the membrane lipid phosphatidylcholine (PC) to DAG. The FA esterified to PC are also the substrate for FA modification (e.g. desaturation, hydroxylation, etc.), such that the FA composition of PC-derived DAG can be substantially different than that of de novo DAG. Since DAG provides two of the three FA in TAG, the relative flux of TAG synthesis from de novo DAG or PC-derived DAG can greatly affect the final oil FA composition. Here we review how the fluxes through these two alternate pathways of DAG/TAG synthesis are determined and present evidence that suggests which pathway is utilized in different plants. Additionally, we present examples of how the endogenous DAG synthesis pathway in a transgenic host plant can produce bottlenecks for engineering of plant oil FA composition, and discuss alternative strategies to overcome these bottlenecks to produce crop plants with designer vegetable oil compositions.